Development of Mobile Learning Application for Science in Children’s Daily Lives - Ayob, Nurul Syazwani; Md Fudzee, Mohd Farhan (Applied Information Technology And Computer Science, 2025)
Science is an important subject that helps children become curious, think critically, and understand how the world works. Learning science at an early age builds a strong foundation and encourages kids to ask questions about everyday things. However, existing science learning apps often rely heavily on text or simple visuals and are mostly in English making them less suitable for children who prefer learning in Malay. To address these gaps, mobile learning application called Celik Sains has been proposed and developed to helps children explore and learn science in their daily lives. The target users for this project are children aged 7 to 12 years old. The Multimedia Mobile Content Development (MMCD) approach is used to develop the Celik Sains application. The usability testing has resulted in an average 81.83 which is within the range of “Acceptable” in the Acceptability Ranges Score Scale, graded “B” on the Grade Scale, and rated “Excellent” based on the System Usability Scale (SUS). This application is expected to assist children in understanding the fundamentals of science. It covers science concepts related to daily life through interactive and engaging activities.